Trends Use of Technology Research for Early Childhood Education: A Bibliometric & Biblioshiny Analysis (1971-2024) - Ramadhani, Atika Miftah; Setiawan, Risky; Gunawan, Resky Nuralisa; Zafrullah, Zafrullah; Ayuni, Rizki Tika (Postgraduate, University of Mataram, 2024)
This study aims to analyze research trends in the use of technology in early childhood education using the Scopus Database. Employing the PRISMA method, the author identified 172 final documents, analyzed through the R Program and VOSviewer. The analysis reveals that research in this area commenced in 1971, with a fivefold increase in publications over the past 20 years. The year 2020 marked the peak with an h-index of 7 and 11 publications (6.39%). Illinois State University emerged as the leading institution with 11 articles (6.39%). The United States is the most productive country, contributing 28 articles (16.28%) and 786 citations (26.85%). Susan Edwards from Australian Catholic University is the most prolific author, achieving an h-index of 5, 253 citations (8.64%), and 5 publications (2.90%). The International Journal of Technology and Design Education is the top source, with 292 citations (9.97%) and 11 publications (6.39%). The document by Blackwell et al. (2014) received the highest citations at 210 (9.02%). The study identified 54 keywords across 7 clusters, recommending